Pengaruh Kualitas Layanan, Citra Perusahaan, Dan Kepercayaan Terhadap Kepuasan Konsumen Pengguna Jasa Ekspedisi J&T Express (Studi Pada Mahasiswa FEB Universitas Islam Malang) - Maulana, Alvi Syahru Badrus; Wahono, Budi; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze the influence of service quality, company image, and trust on customer satisfaction among users of J&T Express services. The research method used is quantitative with purposive sampling technique on students from the Faculty of Economics and Business at the Islamic University of Malang who have used J&T Express courier services. The sample size used was 70 respondents based on the calculation of the number of indicators. The results of the study indicate that the combined influence of service quality, company image, and trust significantly affect customer satisfaction. Partially, service quality and company image have a positive impact on customer satisfaction, while trust does not significantly influence customer satisfaction. Keywords: Service quality, Company image, Trust and Customer satisfaction